First cranial remains of a non-aristonectine elasmosaurid plesiosaur from Antarctica - O'Gorman, José Patricio (2017)
Elasmosaurid plesiosaurs remains are frequently collected across the Marambio Group (Santonian-Danian), Antarctica. Notwithstanding, finding of informative cranial material is extremely rare. A new specimen (MLP 15-I-7-6), from the Cape Lamb Member of the Snow Hill Island Formation (lower Maastrichtian) in Vega Island (Fig. 1.A, B) allows studying the cranial anatomy of Antarctic non-aristonectine elasmosaurids. The preserved parts of the specimen comprises the braincase, the squamosal arch and the posterior half of the palate, all enclose in a single sandstone concretion and associated with cervical, dorsal and caudal vertebrae, and fragmentary girdles and propodials (Fig. 1C). The elongated vertebral centra indicate that MLP 15-I-7-6 is not an aristonectine elasmosaurid. However it shows two features previously recorded only in the aristonectine elasmosaurids Aristonectes quiriquinensis and A. zealandiensis and therefore, considered synapomorphics for that clade (Otero et al., 2014, 2016): absence of posterior interpterygoid, and the presence of a posterior plate-like extension of the pterygoid (Fig. 2, 3). This suggests that such features could not be exclusive of the aristonectine clade. This new record is important because it shows, for the first time, differences between the skull of non-aristonectine elasmosaurids from the Weddellian Province (i.e. Patagonia, Western Antarctica and New Zealand) and those from the Northern Hemisphere. The authors thank to Dirección Nacional del Antártico and the Instituto Antártico Argentino, project: PICTO 2010-0093 (M.R.) and support of the Fuerza Aérea Argentina (Base Marambio, Dotación 46°).